REKONSTRUKSI PROSES DAN MAKNA BELAJAR SOSIAL BERBASIS LINGKUNGAN ETNIK DAYAK (Pemberdayaan Masyarakat Untuk Meningkatkan Keberdayaan Ekologis Pada Kelompok Tani Manuhing Raya) - Silipta (2022)
Masyarakat Dayak di Kalimantan Tengah tidak lepas dari alam. Kehidupan masyarakat Dayak bergantung pada alam. Dalam konteks perilaku ekologis masyarakat Dayak memiliki hubungan yang erat dengan alam. Namun permasalahannya, keadaan alam menjadi terganggu dan menyebabkan terganggunya kehidupan masyarakat Dayak. Alam menjadi rusak oleh karena kelalaian dan keserakahan manusia. Penelitian ini bertujuan untuk mendeskripsikan rekonstruksi belajar sosial berbasis etnik Dayak untuk meningkatkan keberdayaan ekologis pada pemberdayaan masyarakat Kelompok Tani Manuhing Raya. Dalam tujuan ini akan dilihat deskripsi model kegiatan belajar sosial pemberdayaan ekologi oleh masyarakat yang berwawasan lingkungan Etnik pada kelompok tani Manuhing Raya, serta menetapkan langkah mengembangkan model belajar sosial yang berwawasan lingkungan etnik Dayak pada pemberdayaan masyarakat kelompok tani Manuhing Raya. Penelitian ini dilaksanakan dengan alasan bahwa permasalahan masyarakat etnik Dayak di Kalimantan Tengah mengalami masalah dengan lingkungan sebagai mata pencaharian. Untuk itu perlu diperbaharui belajar sosial belajar masyarakat Dayak itu sendiri. Untuk menemukan jawaban atas permasalahan dalam penelitian ini, peneliti menggunakan metode penelitian kualitatif dengan menggali data melalui wawancara, observasi, dan dokumentasi. Temuan dalam penelitian ini adalah: pertama, model belajar sosial pemberdayaan ekologi masyarakat berwawasan lingkungan etnik pada Kelompok Tani Manuhing Raya Kalimantan Tengah dapat diklasifikasikan, yaitu: penyuluhan, pelatihan, dan seminar. Kedua, hasil rekontruksi model belajar sosial yang berwawasan lingkungan etnik Dayak pada pemberdayaan masyarakat Kelompok Tani Manuhing Raya Kalimantan Tengah meliputi rekonstruksi aspek motivasi, emosi, dan tindakan. Implikasi dari ketiga aspek ini kelompok tani Manuhing Raya dalam belajar sosial berbasis etnik dayak dilakukan dengan cara meniru, mencontoh, dan dimotivasi oleh tokoh adat dan tokoh panutan dalam pertanian. Dengan demikian, rekonstruksi konsep belajar sosial anggota kelompok tani tidak cukup dari pengetahuan yang diperoleh sendiri, namun perlu didukung oleh keteladanan tokoh adat dan tokoh ahli di masyarakat yang dapat mengelola ekosistem dan lingkungan alam dengan baik. Kata Kunci : Rekonstruksi, Belajar Sosial, Lingkungan Etnik Dayak ABSTRACT The title of this dissertation is RECONSTRUCTION OF SOCIAL LEARNING PROCESS AND MEANING BASED ON THE DAYAK ETHNIC ENVIRONMENT (Community Empowerment to Increase Ecological Empowerment in Manuhing Raya Farmer Groups). The Dayak community in Central Kalimantan cannot be separated from nature. The life of the Dayak community depends on nature. Inthe context of the ecological behavior of the Dayak community has a close relationship with nature. However, the problem is that the natural conditions are disturbed and cause disruption to the life of the Dayak community. Nature is corrupted by human negligence and greed. This study aims to describe the reconstruction of social learning based on the Dayak ethnic group to increase ecological empowerment in the community empowerment of the Manuhing Raya Farmer Group. In this purpose, a description of the model of social learning activities for ecological empowerment by people with environmental insight will be seen in the Manuhing Raya farmer group, as well as determining the steps to develop a social learning model with an environmental perspective for the Dayak ethnic group in empowering the Manuhing Raya farmer group. This research was conducted on the grounds that the problems of the Dayak ethnic community in Central Kalimantan had problems with the environment as a source of livelihood. For this reason, it is necessary to renew the social learning of the Dayak community itself. To find answers to the problems in this study, researchers used qualitative research methods by digging up data through interviews, observation, and documentation. The findings in this study are: first, the social learning model of ecological community empowerment with an ethnic environment perspective in the Manuhing Raya Farmers Group, Central Kalimantan can be classified, namely: To find answers to the problems in this study, researchers used qualitative research methods by digging up data through interviews, observation, and documentation. The findings in this study are: first, the social learning model of ecological community empowerment with an ethnic environment perspective in the Manuhing Raya Farmers Group, Central Kalimantan can be classified, namely: To find answers to the problems in this study, researchers used qualitative research methods by digging up data through interviews, observation, and documentation. The findings in this study are: first, the social learning model of ecological community empowerment with an ethnic environment perspective in the Manuhing Raya Farmers Group, Central Kalimantan can be classified, namely:pcounseling,training, and seminars.Second, the results of the reconstruction of a social learning model with an environmental perspective of the Dayak ethnic group on the empowerment of the Manuhing Raya Farmers Group in Central Kalimantan include the reconstruction of aspects of motivation, emotion, and action. The implication of these three aspects is that the Manuhing Raya farmer group in Dayak ethnic-based social learning is carried out by imitating, imitating, and being motivated by traditional leaders and role models in agriculture. Thus, the reconstructionthe concept of social learning for members of farmer groups is not enough from the knowledge gained alone, but needs to be supported by the example of traditional leaders and expert leaders in the community who can manage ecosystems and the natural environment well. Keywords: Reconstruction, Social Learning, Dayak Ethnic Environment